2016
DOI: 10.1007/s13762-016-1063-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(amidoamine)-graft-poly(methyl acrylate) magnetic nanocomposite for removal of lead contaminant from aqueous media

Abstract: Poly(amidoamine)-graft-poly(methyl acrylate) magnetic nanocomposite was synthesized via radical polymerization of methyl acrylate onto modified magnetic nanoparticles followed by the functionalization of the methyl ester groups with poly(amidoamine) dendrimer. The resulting poly(amidoamine)-graft-poly(methyl acrylate) magnetic nanocomposite was then characterized by infrared spectroscopy, transmission electron microscopy, thermogravimetric analysis, scanning electron microscope and X-ray diffraction analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…They found that the process of adsorption was pH dependent, and the adsorption capacity order was Pb 2+ > Cu 2+ > Cd 2+ > Ni 2+ , as illustrated in Figure 4 [186]. In another study, magnetic nanocomposites composed of G3-PAMAMgraft-poly (methyl acrylate) were created for the magnetic removal of Pb 2+ ions [187]. At pH 5-6, the maximum adsorption capacity (310 mg/g) was found.…”
Section: Effect Of Solution Phmentioning
confidence: 95%
“…They found that the process of adsorption was pH dependent, and the adsorption capacity order was Pb 2+ > Cu 2+ > Cd 2+ > Ni 2+ , as illustrated in Figure 4 [186]. In another study, magnetic nanocomposites composed of G3-PAMAMgraft-poly (methyl acrylate) were created for the magnetic removal of Pb 2+ ions [187]. At pH 5-6, the maximum adsorption capacity (310 mg/g) was found.…”
Section: Effect Of Solution Phmentioning
confidence: 95%
“…In addition, iron oxide had poor solubility and tended to form iron hydroxide precipitation at low pH value, and it was not easy to form iron oxide gel. Pourjavadi et al (2016) polymerized methyl acrylate on the surface of activated magnetic particles and then grafted PAMAMs with methyl acrylate group to prepare magnetic nanocomposites (PAMAM-MNC). In general, the composite adsorbent obtained by modifying magnetic nano-material with PAMAMs has a certain potential application value for the development of heavy metal adsorption research.…”
Section: Pamams/magnetic Nanomaterials Compositesmentioning
confidence: 99%
“…A. Pourjavadi prepared the PAMAM magnetic nano-hybrid material PAMAM-MNC by this method (Fig. 1b), 18 and the adsorption capacity of Pb 2+ was as high as 310 mg g −1 .…”
Section: Magnetic Adsorption Materials Modified By Organic Small Mole...mentioning
confidence: 99%